HUBUNGAN KOMPLEKSITAS INFORMASI (TRANSAKSI PIHAK BERELASI DAN PENGHINDARAN PAJAK) DAN BIAYA AUDIT - Primadyan, Maretha; fatima, Eliza (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2021)
The purpose of this paper is to examine the relationship of information complexity and audit fee. The complexity of information comes from related party transaction and tax avoidance. Related party transaction are measured by the sum of sales, purchases, loans and loans between related parties. Tax avoidance is measured by Cash ETR. The population of this study is all companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017. The final sample in this study was 241 observations. The results of this study are tax avoidance does not have a positive relationship on audit fee. Then, related party transaction have a positive effect on audit fee. In addition, this study also examined the role of institutional ownership on the relationship of information complexity (related party transaction and tax avoidance) to audit fee. This study reveals that institutional ownership has been shown to weaken the relationship between tax avoidance and audit fee. With the existence of institutional ownership as good external monitoring, the effect of tax avoidance on audit fee is expected to be minimized. Along with monitoring of institutional investors, the risks faced by auditors will be reduced in auditing and this will have an impact on audit fee.